Pharmacokinetics of dalfampridine extended release 7.5‐mg tablets in healthy subjects and individuals with mild and moderate renal impairment: An open‐label study. (22nd October 2013) - Samara, Emil; Winkle, Peter; Pardo, Patricia; Henney, Herbert R.; Way, Susan L.; Brown, Eppie; Lee, Angela; Blight, Andrew R.
Abstract Dalfampridine extended release tablets (D‐ER; prolonged‐release fampridine in Europe) are available to improve walking in patients with multiple sclerosis (MS). D‐ER is mainly renally eliminated; the approved 10‐mg twice daily dose is contraindicated in the United States in patients with moderate or severe renal impairment. This study evaluated single‐dose and steady‐state pharmacokinetics of a 7.5‐mg dose of D‐ER in healthy subjects (n = 13) and subjects with mild (n = 17) and moderate (n = 12) renal impairment. D‐ER plasma concentrations were consistently higher in subjects with renal impairment relative to healthy individuals with a significant (P < .0001) inverse linear relationship between creatinine clearance and drug exposure. Steady‐state AUC0–12 among healthy subjects, 167.0 ± 55.3 ng h/mL, increased 74% and 151% with mild and moderate renal impairment, respectively. The overall incidence of adverse events was 61.5%, 47.1%, and 33.3% in healthy subjects, and subjects with mild and moderate renal impairment, respectively, and for treatment‐related adverse events the rates were 0%, 17.6%, and 8.3%, respectively. The most common adverse events were headache, dizziness, and arthralgia. The pharmacokinetics of D‐ER 7.5‐mg twice daily in subjects with mild renal impairment was comparable to 10‐mg twice daily in patients with MS who had normal renal function. Exposure was significantly higher in moderate renal impairment.